Digital Leadership And Organizational Agility: Examining The Role Of Artificial Intelligence Adoption In Enhancing Strategic Performance - Klemens Mere (Community Engagement and Emergence Journal (CEEJ), 2026)
The rapid development of digital technology has significantly transformed organizational management and strategic decision-making processes. Digital leadership has emerged as a critical capability for organizations to navigate complex and dynamic environments. This study aims to examine the relationship between digital leadership and organizational agility, with a particular focus on the role of artificial intelligence (AI) adoption in enhancing strategic performance. The research employs a literature review method by analyzing scholarly articles published between 2020 and 2025 from reputable academic databases. The review highlights how digital leadership facilitates technological integration, promotes data-driven decision making, and encourages innovation within organizations. Furthermore, the adoption of AI is identified as a key enabler that strengthens organizational agility by improving operational efficiency, predictive capabilities, and strategic responsiveness to market changes. The findings indicate that organizations led by digitally competent leaders are more capable of leveraging AI technologies to support strategic initiatives and maintain competitive advantage. In addition, the synergy between digital leadership and AI adoption contributes to more adaptive organizational structures and improved strategic performance outcomes. This study contributes to the growing body of knowledge on digital transformation by emphasizing the strategic importance of leadership capabilities in maximizing the benefits of artificial intelligence in modern organizations.